The Impact of Guided Inquiry Model on Acquiring Soccer Trapping and Passing Skills for College Students - Mohammed Nasseer Falih (Pubmedia Jurnal Pendidikan Olahraga, 2026)
The purpose of the investigation was to determine the effect of Guided Inquiry Model on teaching football trapping and passing skills. 1.1. Objective of the Study. The goal was also to establish the difference between experimental and control groups of specifications. The researcher employed an experimental design that utilized both pretest and posttest. The participating section consisted of (150) students who are the first stage in the College of Physical Education and Sports Sciences for the year 2025-2026 are distributed over the six sections. A total of 40 students were taken as the primary experimental sample from sections D and F. They were divided into two groups (Experimental group (20 students) – Control group (20 students). After the pretesting, the experimental group received treatment in the form of training consisting of 8 educational units based on the Guided Inquiry Model, which was implemented at the rate of 2 units per week. The results showed that this research proven the Guided Inquiry Model contributes to learning catching and passing the ball skills. Additionally, the model also assists students to build knowledge and cognitive engagement through the learning activity. The study’s recommendation to teach the football skill of trapping and passing is to use the educational curriculum of Guided Inquiry Model. It further recommends conducting additional investigations to assess the appropriateness of this model on additional team sports.